Effect of Chlorhexidine Application Protocol on Durability of Marginal Seal of Class V Restorations - Anna Saffarpuor; Aida Saffarpour; Mohammad Javad Kharazifard; Atoossa Entezamirad Rad (Tehran University of Medical Sciences, 2016)
Objectives: This study aimed to evaluate the effect of chlorhexidine (CHX) application protocol on durability of marginal seal of class V composite restorations. Materials and Methods: Class V cavities (4×2×1.5mm) were prepared in the buccal surfaces of 160 human third molars. The teeth were randomly divided into five groups (n=32) of (G1) CHX+rinse+etching, (G2) CHX+etching, (G3) etching+CHX+rinse, (G4) etching+ CHX, and (G5) etching alone as the control group. Adper Single Bond 2 was applied as an etch and rinse (E & R) bonding system. Cavities were filled with Z350 composite. Half of the teeth in each group were stored in distilled water for 24 hours and the other half were thermocycled (10,000 cycles, 5-55˚C). For dye penetration test, the teeth were sectioned buccolingually and assessed at the enamel and dentin margins under a stereomicroscope at ×20 magnification. The Kruskal-Wallis, Dunn and Mann-Whitney tests were used for statistical analyses. Results: There was no significant difference in immediate microleakage among the groups at the enamel and dentin margins (P= 0.894). After thermocycling, there was significantly less microleakage in G4 than the control group at dentin margin. There were significant differences in microleakage between G4 and G1(P=0.002), G4 and G2 (P=0.001) and G4 and G5 (P= 0.001) at dentin margin. Conclusions: Application of CHX after etching without rinsing is effective to decrease microleakage. However, it has no effect if applied before etching in use of this particular type of E & R adhesive after thermocycling.